Product development using CNC lathe machine / Royhaila Drahman, Nazifah Muti and Zaiton Jahaya - Drahman, Royhaila; Muti, Nazifah; Jahaya, Zaiton (Faculty of Mechanical Engineering, 1990)
Many of the achievements in computer aided design (CAD) and Computer aided manufacturing (CAM) have a common origin in numerical control. Today there is a large number of different types of numerically controlled (NC) machine tools available. The NC technology is of great importance for automated manufacturing .